(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Merauke Regency is located in the southern part of Papua, directly adjacent to Papua New Guinea. It has a mangrove ecosystem that is still good (pristine) which is quite extensive and rich in molluscs and crustaceans which are key fauna in the mangrove ecosystem. The aims of this research were to know the structure of molluscs and crustaceans community in mangrove ecosystem in this area. A study was conducted in October 2019 in 13 stations. Molluscs and crustaceans sample were collected in each location using a plot measuring 10 x 10 m. Samples were taken for 20 minutes by the same two people in each plot at low tide. From this study found 11 species of the crustaceans and 6 species of the molluscs. Cerithidea obtusa, Littoraria scabra and Cassidula angulifera of the molluscs group were macrobenthos that had a relatively wide distribution. The highest abundance was found in MRKM22 station (5.67 individuals/m2) and the lowest was in MRKM33 (0.25 individuals/m2). The molluscs and crustaceans found in this study were common species in mangrove ecosystem. The value of species diversity index (H’) ranged from 0.63 to 1.56. This value indicated the diversity of molluscs and crustaceans species was of low-moderate condition. Evenness index (J’) ranged from 0.56 to 0.99 and dominance index (C) ranged from 0.24 to 0.56. In general, these ecological values showed that the molluscs and crustaceans community in each station is in a relatively stable condition.